FINANCIAL AWARENESS AND BUDGETING PRACTICES OF A PRINTING AND LABELING COMPANY - Kandpal, Naina; Chavan, Vishal; Sharma, Bhawana (International Journal of Research -GRANTHAALAYAH, 2025)
The study examines financial literacy and budgeting specifically in the printing and labeling industry. Through the administration of a questionnaire to the employees, the study would examine what they understand about the budgetary process, the financial management issues presented in the company as well as the existing financial controls. After an extensive survey and data examination, it was found that a lack of training, ineffectively utilized resources, and gaps in communication were cited, and these issues are elaborated further in the paper. Some of the recommended initiatives are enhanced financial literacy programs, tracking tools available when needed, and better departmental collaboration to achieve reasonable budget accuracy. The final goal of this research is to have original recommendations and ideas as a basis for accountability and enhancements in financial management at the institution.